Understanding teamwork errors in royal air force air traffic control. (November 2018) - Read, Kate; Charles, Rebecca
Highlights: TRM is not yet being embraced in RAF ATC. Deficiencies identified through evaluation of incident reports and interviews. Controllers have a strong sense of team cohesion. Understand the required behaviours for successful teamwork. There is limited appreciation among the controllers regarding cognitive aspects of teamwork. Abstract: Despite the success of Crew Resource Management (CRM) training in aviation and the development and implementation of Team Resource Management (TRM) in civil Air Traffic Management (ATM), the Royal Air Force (RAF) is yet to embrace a dedicated, Air Traffic Control (ATC)-specific TRM training programme for its controllers. In order to ascertain the extent to which teamwork-related errors are contributing to RAF ATM incidents, the first part of this study involved analysis of data from incident reports. Using the outputs from the first study, the second part of the study involved interviews with current controllers at Terminal Units in order to understand their perceptions of team, teamwork and teamwork errors in ATC and identify any deficiencies. Both co-located and geographically dislocated teams were considered. The findings showed that controllers have a strong sense of team cohesion and understand the behaviours required for successful teamwork, but have limited appreciation for the cognitive aspects of teamwork, which is where errors are manifesting in incidents. This improved understanding of deficiencies will provide a foundation for future RAF ATC TRM training development.